Recovery of interest in enforcement procedure in the Republic of Slovenia - Merc, Irena (Lexonomica, 2021)
In Slovenian enforcement procedures, the principle of formal legality applies, so the enforcement court is bound by the enforceable title. The court must allow the enforcement of the claim as it follows from the enforceable title. The creditor also needs an enforceable title to claim interest. Interest arising from a Slovenian enforceable title shall be executed at the interest rate specified in Slovenian legislation. In the Republic of Slovenia, interest arising from a foreign enforceable title takes place at the interest rate determined by a foreign substantive provision. If the interest rate is determinable in a foreign enforceable title, the Slovenian Enforcement Court shall concretise the obligation by determining the interest rate determined by foreign law before issuing the writ of execution.
Keywords: certificate of enforceability; concretisation of obligations; interest; principle of formal legality; suitability of the enforceable title for the enforcement; two-stage enforcement procedure